Kappa but not delta or mu opioid receptors form homodimers at low membrane densities - Cechova, Kristina; Lan, Chenyang; Macik, Matus; Barthes, Nicolas P F; Jung, Manfred; Ulbrich, Maximilian H (Cellular and molecular life sciences, 2021)
Opioid receptors (ORs) have been observed as homo- and heterodimers, but it is unclear if the dimers are stable under physiological conditions, and whether monomers or dimers comprise the predominant fraction in a cell. Here, we use three live-cell imaging approaches to assess dimerization of ORs at expression levels that are 10-100 × smaller than in classical biochemical assays. At membrane densities around 25/µm2, a split-GFP assay reveals that κOR dimerizes, while µOR and δOR stay monomeric. At receptor densities < 5/µm2, single-molecule imaging showed no κOR dimers, supporting the concept that dimer formation depends on receptor membrane density. To directly observe the transition from monomers to dimers, we used a single-molecule assay to assess membrane protein interactions at densities up to 100 × higher than conventional single-molecule imaging. We observe that κOR is monomeric at densities < 10/µm2 and forms dimers at densities that are considered physiological. In contrast, µOR and δOR stay monomeric even at the highest densities covered by our approach. The observation of long-lasting co-localization of red and green κOR spots suggests that it is a specific effect based on OR dimerization and not an artefact of coincidental encounters.
Keywords: Monomer-dimer equilibrium; Animals; analýza jednotlivých buněk; Single Molecule Imaging; G protein-coupled receptors; Opioid receptors; Mice; receptory opiátové delta; Receptors, Opioid, delta; zobrazení jednotlivé molekuly; myši; Protein Multimerization; Receptors, Opioid, mu; Protein Conformation; konformace proteinů; krysa rodu Rattus; receptory opiátové mu; Dimerization affinity; Single-molecule imaging; multimerizace proteinu; zvířata; buněčná membrána; Single-Cell Analysis; Rats; Cell Membrane